1974
DOI: 10.1111/j.1399-3054.1974.tb03721.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Conditions, Metabolic Inhibitors, and Phenolic Compounds on the ATP Pool in Fomes annosus

Abstract: The ATP pool of growing fungal mycelia, particularly Fomes annosus, has been determined. The ATP level varied during the different growth phases and correlated with the variations in the economic coefficient. Common uncouplers (at concentrations similar to those used in mitochondrial tests) decreased the ATP pool very rapidly. The size of the pool often fell 50–80% before the O2 uptake decreased below that of the control and was accompanied by an increasing exudation of inorganic phosphate. Phenolic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Of the different lignin preparations poor laccase activity in the presence of reax can be attributed to its degree of sulfonation (4.7% as mentioned by its manufacturers, Westvaco Chemical Division, U.S.A.) as lignosulfonates have been shown to be poorly utilized as compared to kraft lignin (ANDER and ERIKSSON 1978). Laccase induced is suggested to detoxify the phenolic compounds (GRABBE et al 1968, JOHANS-SON andHAGERBY 1974) and cause demethylation of lignin, a key step for its degradation (TROXANOWSKI andLEONOWICZ 1969, KIRK andCHANG 1975). Salicylic acid inhibited enzyme as well as biomass production in both the fungi (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Of the different lignin preparations poor laccase activity in the presence of reax can be attributed to its degree of sulfonation (4.7% as mentioned by its manufacturers, Westvaco Chemical Division, U.S.A.) as lignosulfonates have been shown to be poorly utilized as compared to kraft lignin (ANDER and ERIKSSON 1978). Laccase induced is suggested to detoxify the phenolic compounds (GRABBE et al 1968, JOHANS-SON andHAGERBY 1974) and cause demethylation of lignin, a key step for its degradation (TROXANOWSKI andLEONOWICZ 1969, KIRK andCHANG 1975). Salicylic acid inhibited enzyme as well as biomass production in both the fungi (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…While it is clear that more work is needed on the respiratory action of various flavonoids implicated in allelopathy, even a small interference with ATP production in the intact plant could impact growth. Johansson and Hagerby (77) reported that phenolic acids lowered the ATP pool of growing fungal mycelia, but that relationship to growth was unclear. Table II data show the concentration of phenolic acids required to inhibit mitochondrial oxygen uptake is several orders of magnitude higher than flavonoids.…”
Section: Allelochemical Interference With Respirationmentioning
confidence: 98%
“…According to some authors, a negative interactions allelopathic species of the Cirsium genus (C. arvense, C. japonicum), probably due to the release by their organs phenolic compounds (Kovacs et al, 1988;Kazinczi et al, 2001;Chon et al, 2003). Phenols have inhibiting influence, among others on -ATP synthesis in mitochondria and photosynthesis (Stenlid, 1970;Johansson and Hägerby, 1974;Dadkhah, 2012). They increase the permeability of cell membranes by their depolarisation and inhibition of protein synthesis and play an important role in supplying plants with nutrients (Baziramakenga et al, 1995).…”
Section: Discussionmentioning
confidence: 99%